Influence of crystal structure on size dependent deformation behavior and strain heterogeneity in micro-scale deformation. (July 2019) - Tang, X.F.; Peng, L.F.; Shi, S.Q.; Fu, M.W.
Abstract: Crystal structure determines the distinct deformation mode of crystalline materials and thus plays a critical role in micro-scale deformation. The micro-deformation mechanism at grain level, however, is still not well understood and the knowledge of how crystal structure affects size effect and its affected deformation behaviors in micro-scale deformation is not yet systematic and extensive enough to support micro-manufacturing and microproduct development. To explore the influence of crystal structure on size dependent deformation, strain heterogeneity and fracture in micro-scale deformation, a series of micro-scale tensile tests using polycrystalline pure copper (FCC), pure iron (BCC) and pure α-titanium (HCP) sheets with various thicknesses and microstructural grain sizes were conducted. A mechanism-based crystal plasticity (CP) model incorporating size-dependent slip and twinning was proposed. The CP model successfully predicted the influence of grain size and thickness on the flow stress as well as the dependence of twinning volume fraction on the grain size of Ti samples. Full-field simulation was carried out to thoroughly explore the influence of crystal structure on grain-scale strain heterogeneity and fracture behavior via examining strain localization, lattice rotation, slip and twinning activity. Results showed that when only few grains exist in the thickness direction, slip activation is particularly limited in HCP Ti sample, leading to strain concentration and generation of wide and long shear bands thus sharply reduce the fracture toughness. Lattice rotation of Cu samples is most uniform. The large strain in samples of BCC Fe is distributed more dispersedly and more shear bands are formed. This work presents a comprehensive understanding of the effect of crystal structure on the size effect affected micro-scale deformation of metallic materials at grain level and a basis to support the applications of micro-scale deformation for making different crystal structured micro-parts. Highlights: A mechanism-based crystal plasticity model incorporating size-dependent slip and twinning was proposed. Influence of crystal structure on size dependent deformation behavior in micro-scale deformation was first explored. Many short shear bands are evenly distributed in the samples with a large ratio of thickness to grain size. Slip activity is especially limited in HCP Ti sample and long shear bands are formed when only few grains bear the strain. Large strain is most dispersedly distributed in the samples of BCC Fe and more shear bands are formed in BCC Fe samples.